Regioselective Markovnikov hydrodifluoroalkylation of alkenes using difluoroenoxysilanes - Hu, Xiao-Si (Nat Commun, 2020)
Alkene hydrodifluoroalkylation is a fruitful strategy for synthesizing difluoromethylated compounds that are interesting for developing new medicinal agents, agrochemicals, and advanced materials. Whereas the anti-Markovnikov hydrodifluoroalkylation to linear-type products is developed, employing radical-based processes, the Markovnikov synthesis of branched adducts remains unexplored. Herein, we describe acid-catalyzed processes involving carbocation intermediates as a promising strategy to secure the Markovnikov regioselectivity. Accordingly, the Markovnikov hydrodifluoroalkylation of mono-, di-, tri-, and tetrasubstituted alkenes using difluoroenoxysilanes, catalyzed by Mg(ClO(4))(2)·6H(2)O, is achieved. This allows the diversity-oriented synthesis of α,α-difluoroketones with a quaternary or tertiary carbon at the β-position that are otherwise difficult to access. The method is applied to the modification of natural products and drug derivatives. The resulting α,α-difluorinated ketones could be converted to the corresponding α,α-difluorinated esters or alcohols, or organofluorine compounds featuring a CF(2)H or CF(2)CF(2)Ph moiety. Mechanistic studies support that Mg(ClO(4))(2)·6H(2)O functions as a hidden Brønsted acid catalyst.